2005
DOI: 10.1007/s00418-005-0092-y
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Toll-like receptor 4 expression in mouse colon by macrophage migration inhibitory factor

Abstract: Recent studies have indicated that macrophage migration inhibitory factor (MIF) and Toll-like receptor (TLR) play an important role in the regulation of innate immune responses. In this study, we investigated the effect of MIF on the expression of TLR4, a receptor that recognizes lipopolysaccharide, in colon using MIF-deficient mice. TLR4 mRNA expression in the colon tissues was determined by northern blot analysis. Western blot analysis and immunohistochemistry in the colon tissues were performed to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 36 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…33 TLR4 was upregulated in patients with IBD 34 and colitis model. 35 NF-κB was also upregulated in TNBSinduced colitis. 2 In line with previous study, 36 the present study showed that TNBS stimulated TLR4/NF-κB activation, thus leading to release of proinflammatory factors and promotion of inflammatory response.…”
Section: Discussionmentioning
confidence: 91%
“…33 TLR4 was upregulated in patients with IBD 34 and colitis model. 35 NF-κB was also upregulated in TNBSinduced colitis. 2 In line with previous study, 36 the present study showed that TNBS stimulated TLR4/NF-κB activation, thus leading to release of proinflammatory factors and promotion of inflammatory response.…”
Section: Discussionmentioning
confidence: 91%
“…TLR4 is activated by recognizing PAMPs in bacteria, which in turn triggers signaling cascades leading to the activation of NF-κB (12). TLR4 is expressed at low levels in normal intestines but is increased in mice with DSS-induced colitis (13,14) and in patients with IBD (15,16), which may contribute to the initiation or perpetuation of intestinal inflammation. Previous studies have demonstrated that TLR4 functions as a mediator of intestinal inflammation (17) and that the blockade of TLR4 ameliorates DSS-induced colitis (18).…”
Section: Discussionmentioning
confidence: 99%
“…Upon ligand binding, TLR4 undergoes a conformational change and dimerizes, recruiting adaptor proteins, such as myeloid differentiation primary response gene 88 (MyD88), which in turn activates NF-κB, transducing the immune-related signals to the nucleus (10,11). Due to its essential role in the pathogenesis of inflammatory diseases, including IBD (12)(13)(14)(15)(16)(17)(18), modulation of the TLR4/NF-κB signaling pathway may be a main target for the treatment of inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, both human TLR-2 and -9 antibodies very effectively detected the presence of porcine TLR-2 and -9 in the ileal tissues from all the three groups of animals; however, we were unable to detect porcine TLR-4 and -5 with polyclonal human TLR-4 and -5 antibodies. One possible explanation might be a longer fixation of ileal tissues for 48 hours in formalin in the present study compared to 16 hours used in earlier studies [42,69]. This might have resulted in non-retrieval of TLR-4 and -5 antigens with the treatment procedure used in this study.…”
Section: Discussionmentioning
confidence: 85%